Essays on the Economics of Migration: an Empirical Perspective - Fiore, Simona <1984> (Alma Mater Studiorum - Università di Bologna, 2016)
This thesis comprises three essays on determinants and consequences of international labor migration at individual, family and country level. The first chapter explores the effect of parents' absence due to migration on the educational outcomes of children left behind. The estimated reduced form model relies on an educational production function where the total effect of migration is the combination of the positive effect of remittances, and the negative effect of a parent's absence. The results suggest that parental absence offsets the positive impact of remittances on children's schooling achievements and that a mother's absence is more detrimental than a father's absence. The second chapter examines the effects of family size and demographic structure on offspring's international migration. The potential endogeneity of parental fertility choices is addressed by using infertility shocks and miscarriage before first birth as exogenous variation in family size. The positive correlation between fertility and migration disappears when the potential endogeneity of sibship size is addressed. A deeper analysis reveals that the chances to migrate are not equally distributed across children within the family. Older siblings are more likely to migrate, while having more sisters than brothers may increase the chances of migration, particularly among girls. The third chapter studies the effect of granting the right to vote in local elections to non citizens of non Eu origin. In the spirit of a differences-in-differences strategy, election results and economic outcomes of municipalities with more immigrants entitled to vote are compared with municipalities with a smaller share of immigrant voters, before and after the introduction of a new law. Preliminary results indicate that, depending on the economic and demographic context, and on the immigration policies, the effect can vary substantially: the pro immigrants parties can either gain on lose votes, with relevant consequences for public good expenditures.